Is female sex an independent predictor of in-hospital mortality in acute myocardial infarction? - Pimenta,Lúcia (2001)
OBJECTIVE: To assess whether female sex is a factor independently related to in-hospital mortality in acute myocardial infarction. METHODS: Of 600 consecutive patients (435 males and 165 females) with acute myocardial infarction, we studied 13 demographic and clinical variables obtained at the time of hospital admission through uni- and multivariate analysis, and analyzed their relation to in-hospital death. RESULTS: Females were older (p<0.001) and had a higher incidence of hypertension (p<0.001). Males were more frequently smokers (p<0.001). The remaining risk factors had a similar incidence among both sexes. All variables underwent uni- and multivariate analysis. Through univariate analysis, the following variables were found to be associated with in-hospital death: female sex (p<0.001), age >70 years (p<0.001), the presence of previous coronary artery disease (p=0.0004), previous myocardial infarction (p<0.001), infarction in the anterior wall (p=0.007), presence of left ventricular dysfunction (p<0.001), and the absence of thrombolytic therapy (p=0.04). Through the multivariate analysis of logistic regression, the following variables were associated with in-hospital mortality: female sex (p=0.001), age (p=0.008), the presence of previous myocardial infarction (p=0.02), and left ventricular dysfunction (p<0.001). CONCLUSION: After adjusting for all risk variables, female sex proved to be a variable independently related to in-hospital mortality in acute myocardial infarction.